New History of Uzbekistan Inspired by the Gloss of Colors - Professor Turgunoy Egamberdiyeva; Dzhalilova Rozikhan Kazakovna (Zien Journals, 2023)
The composition of the new history of Uzbekistan, painting and drawing, was analyzed scientifically, practically and theoreticallyYears of independence fine art personal exhibitions creative bees. Methods of teaching in schools of fine arts, methods of the history of illustration are considered step by step
Keywords: Personal exhibitions; World; parent child